Water-retaining and sand-fixing biomass hydrogel material with function of monitoring water content

By introducing MXene conductive material into the water-retaining and sand-fixing hydrogel, combining the biomass materials itaconic acid and artemisia granulated, real-time water content monitoring and mechanical properties of the hydrogel are achieved, and the problems of hydrogel monitoring gaps and environmental pollution in the prior art are solved.

CN119899319AActive Publication Date: 2025-04-29SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510094427.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

There are technical gaps in the existing water-retaining and sand-fixing hydrogels in real-time water monitoring, and are prepared from chemical polymer materials, which poses a risk of environmental pollution.

Method used

The biomass hydrogel material composed of itaconic acid, artemisia gel, initiator, crosslinker and MXene nanosheets is used to monitor the resistance changes of the hydrogel through the conductive properties of MXene, monitor the water content in real time, and reduce the risk of environmental pollution through biomass materials.

Benefits of technology

Real-time monitoring of the water content of the hydrogel is achieved, improving the mechanical properties and biodegradability of the hydrogel, and avoiding the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005252464370000071
    Figure BDA0005252464370000071
  • Figure BDA0005252464370000081
    Figure BDA0005252464370000081
Patent Text Reader

Abstract

The invention discloses a water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function, and belongs to the field of water-retaining and sand-fixing hydrogel, the water-retaining and sand-fixing biomass hydrogel material comprises the following components: itaconic acid, sa-hao seed gum, an initiator, a cross-linking agent and MXene nanosheets; under the action of an initiator and a cross-linking agent, itaconic acid, sa-hao seed gum and MXene nanosheets are polymerized to obtain (polyitaconic acid-sa-hao seed gum) / MXene hydrogel, and the (polyitaconic acid-sa-hao seed gum) / MXene hydrogel is water-retaining and sand-fixing biomass hydrogel with a water content monitoring function. Aiming at the blank of the existing water-retaining and sand-fixing hydrogel in the aspect of real-time water quantity monitoring, the invention prepares the water-retaining and sand-fixing hydrogel capable of monitoring the water content in real time by mainly introducing an MXene conductive material, and aims to provide water for vegetation and monitor the self water content in real time at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water-retaining and sand-fixing hydrogels, and relates to a water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function. Background Art

[0002] Water-retaining and sand-fixing hydrogels can help plants lock in water and thus increase vegetation coverage, which is of great significance to improving land desertification. Existing technologies have conducted certain research on improving the water-holding, mechanical, and antifreeze properties of water-retaining and sand-fixing hydrogels, but to date, no technology has conducted relevant research on real-time water volume monitoring of water-retaining and sand-fixing hydrogels. In arid desert areas with large temperature differences between day and night, the water loss of hydrogels is often large. If the water cannot be replenished in time, it will cause plants to lose water and die.

[0003] In addition, most of the raw materials used in the existing technology for preparing water-retaining and sand-fixing hydrogels are acrylic chemical materials. Chemical polymer materials will gradually degrade and produce monomer substances that are harmful to the environment when used in harsh environments such as long-term high temperature, strong ultraviolet exposure and wind erosion, posing a risk of secondary pollution. Summary of the invention

[0004] The purpose of the present invention is to provide a water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function, thereby solving the problem that the current water-retaining and sand-fixing hydrogel has a technical gap in real-time water volume monitoring, and that the current water-retaining and sand-fixing hydrogel is mainly made of chemical polymer materials, which poses a risk of environmental pollution.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function includes the following components: itaconic acid, artemisia gum, an initiator, a cross-linking agent, and MXene nanosheets;

[0007] Under the action of initiator and cross-linking agent, itaconic acid, artemisia gum and MXene nanosheets are polymerized to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel. The (polyitaconic acid-artemisia gum) / MXene hydrogel is a water-retaining and sand-fixing biomass hydrogel with the function of monitoring water content.

[0008] In view of the gap in real-time water monitoring in existing water-retaining and sand-fixing hydrogels, the present invention mainly introduces MXene conductive materials to prepare a water-retaining and sand-fixing hydrogel that can monitor the water content in real time, aiming to provide water to vegetation while being able to monitor its own water content in real time. When the water content is low due to high water consumption in the environment, the staff can replenish water in time according to the monitoring signal, thereby continuously providing water to vegetation in the desert. The surface of MXene conductive materials is rich in active groups such as -OH, which can form a strong force with itaconic acid and wormwood gum, and can play a good role in enhancing mechanical properties when dispersed in hydrogels.

[0009] The present invention uses biomass materials itaconic acid and artemisia gum as basic skeleton structural units of hydrogel, and introduces MXene conductive material in the preparation process of polyitaconic acid-artemisia gum biomass hydrogel system to prepare (polyitaconic acid-artemisia gum) / MXene hydrogel, and monitors the resistance change of hydrogel through the conductive property of MXene, thereby reflecting the real-time water content of hydrogel and improving the mechanical properties of hydrogel; specifically, when the water content in hydrogel increases, the number of hydrogen bonds between MXene and water molecules increases, the conductive network is more complete, the resistance value decreases, and the conductivity increases; conversely, when the water content decreases, the number of hydrogen bonds decreases, the conductive network becomes incomplete, the resistance value increases, and the conductivity decreases; therefore, by monitoring the change of resistance value or conductivity, the water content in hydrogel can be judged.

[0010] In addition, the present invention uses biomass raw materials itaconic acid and artemisia gum to synthesize hydrogel, which gives the hydrogel good biodegradability and avoids secondary pollution to the environment; and the carboxyl density of itaconic acid is higher than that of acrylic acid, which will give the hydrogel better water absorption and moisturizing properties; artemisia gum is a natural polysaccharide with strong viscosity and has tight adhesion to loose sand particles.

[0011] Furthermore, the mass ratio of itaconic acid, artemisia gum, and MXene nanosheets is 13:1:2.

[0012] Furthermore, the initiator is ammonium persulfate, and the amount of the initiator added is 10% of the mass of the artemisia gum.

[0013] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide, and the amount of the cross-linking agent added is 0.1%-0.2% of the mass of itaconic acid.

[0014] Furthermore, the MXene nanosheets are prepared by the following method:

[0015] Lithium fluoride was dissolved in 9 mol / L HCl solution, Ti3AlC2 was added under stirring in an ice bath, the mixture was stirred evenly and then placed in a 40°C oil bath for etching for 48 h. After etching, the solution was centrifuged and washed with deionized water, and the precipitate was collected by centrifugation. The precipitate was added with deionized water and transferred into a washing bottle, and a nitrogen gas source was connected for bubbling. After ultrasonic treatment for 2 h, the solution was centrifuged, and the upper liquid was collected to obtain a MXene solution. The MXene solution was freeze-dried to obtain MXene nanosheets.

[0016] Furthermore, the mass ratio of lithium fluoride to Ti3AlC2 is 1.6:1.

[0017] The water-retaining and sand-fixing biomass hydrogel material having a function of monitoring water content is prepared by the following method:

[0018] S1. Preparation of MXene nanosheets;

[0019] S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: Add artemisia gum to a reaction vessel, then add NaOH solution and stir to form a uniform dispersion. Under nitrogen protection, heat the dispersion to 70°C and stir at a constant temperature for 1.5h, then add an aqueous solution of APS initiator, continue stirring for 25min, and reduce the reaction temperature to 50°C to obtain a reaction system.

[0020] Itaconic acid, NaOH solution containing MBA cross-linking agent and MXene nanosheets are dispersed in water to obtain a suspension, and then the suspension is added dropwise to the reaction system. After the addition is completed, the reaction system is slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction is completed, water is added for washing to obtain a hydrogel system. Finally, glycerol is added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel.

[0021] In the present invention, itaconic acid is polymerized to form polyitaconic acid, which is used together with artemisia gum as the molecular main chain of the hydrogel, with the crosslinking agent MBA as the crosslinking point. The hydroxyl groups on the MXene nanosheets and the carboxyl groups on the side chains of the polyitaconic acid molecules form a strong force through hydrogen bonding and are dispersed in the hydrogel to form a good mechanical reinforcement effect. At the same time, the MXene nanosheets also give the hydrogel good conductive properties. By monitoring the resistance change of the hydrogel, the change of the water content of the hydrogel itself can be monitored.

[0022] Furthermore, the concentration of the NaOH solution in the NaOH solution containing the MBA cross-linking agent is 8 mol / L.

[0023] Furthermore, the artemisia gum was added into a four-necked flask, and then a NaOH solution with a concentration of 0.067 mol / L was added and stirred to form a uniform dispersion.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] 1. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function of the present invention uses biomass materials itaconic acid and artemisia gum as the basic skeleton structural units of the hydrogel, and introduces MXene conductive materials in the preparation process of the polyitaconic acid-artemisia gum biomass hydrogel system to prepare (polyitaconic acid-artemisia gum) / MXene hydrogel, and monitors the resistance change of the hydrogel through the conductive property of MXene, thereby reflecting the real-time water content of the hydrogel;

[0026] 2. The present invention uses biomass raw materials itaconic acid and artemisia gum to synthesize hydrogel, which gives the hydrogel good biodegradability and avoids secondary pollution to the environment;

[0027] 3. In the present invention, the hydroxyl groups on the MXene nanosheets and the carboxyl groups on the side chains of the polyitaconic acid molecules form a strong force through hydrogen bonding, which is dispersed in the hydrogel to form a good mechanical reinforcement effect. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0029] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0030] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0031] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0032] The embodiment of the present invention provides a water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function, comprising the following components: itaconic acid, artemisia gum, an initiator, a cross-linking agent, and MXene nanosheets;

[0033] Under the action of initiator and cross-linking agent, itaconic acid, artemisia gum and MXene nanosheets are polymerized to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel. The (polyitaconic acid-artemisia gum) / MXene hydrogel is a water-retaining and sand-fixing biomass hydrogel with the function of monitoring water content.

[0034] Preferably, the mass ratio of itaconic acid, artemisia gum and MXene nanosheets is 13:1:2.

[0035] Preferably, the initiator is ammonium persulfate, and the amount of the initiator added is 10% of the mass of the artemisia gum. The initiator can also be an initiator of a redox system, such as potassium persulfate-sodium bisulfite.

[0036] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide, and the amount of the cross-linking agent added is 0.1%-0.2% of the mass of itaconic acid.

[0037] Preferably, the MXene nanosheets are prepared by the following method:

[0038] Lithium fluoride was dissolved in 9 mol / L HCl solution, Ti3AlC2 was added under stirring in an ice bath, the mixture was stirred evenly and then placed in a 40°C oil bath for etching for 48 h. After etching, the solution was centrifuged and washed with deionized water, and the precipitate was collected by centrifugation. The precipitate was added with deionized water and transferred into a washing bottle, and a nitrogen gas source was connected for bubbling. After ultrasonic treatment for 2 h, the solution was centrifuged, and the upper liquid was collected to obtain a MXene solution. The MXene solution was freeze-dried to obtain MXene nanosheets.

[0039] Preferably, the mass ratio of lithium fluoride to Ti3AlC2 is 1.6:1.

[0040] The method for preparing the water-retaining and sand-fixing biomass hydrogel material having the function of monitoring water content comprises the following steps:

[0041] S1. Preparation of MXene nanosheets;

[0042] S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: Add artemisia gum to a reaction vessel, then add a NaOH solution with a concentration of 0.067 mol / L and stir to form a uniform dispersion. Under nitrogen protection, heat the dispersion to 70°C and stir at a constant temperature for 1.5 hours, then add an aqueous solution of APS initiator, continue stirring for 25 minutes, and reduce the reaction temperature to 50°C to obtain a reaction system.

[0043] Itaconic acid, a NaOH solution containing an MBA cross-linking agent and MXene nanosheets are dispersed in water to obtain a suspension, wherein the concentration of the NaOH solution in the NaOH solution containing an MBA cross-linking agent is 8 mol / L. The suspension is then added dropwise to the reaction system. After the addition is completed, the reaction system is slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction is completed, water is added for washing to obtain a hydrogel system. Finally, glycerol is added to the obtained hydrogel system and stirred evenly to obtain a (polyitaconic acid-artemisia gum) / MXene hydrogel.

[0044] Example 1

[0045] The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function provided in a specific embodiment of the present invention is prepared by the following method:

[0046] S1. Preparation of MXene nanosheets: Dissolve 1.6 g lithium fluoride in 20 mL 9 mol / L HCl solution, stir in an ice bath, add 1.0 g Ti3AlC2, stir evenly, and then dissolve in a 40°C oil bath for etching for 48 h; after etching, centrifuge the solution, wash with deionized water, and collect the precipitate by centrifugation; add deionized water to the precipitate, transfer it to a washing bottle, connect a nitrogen gas source for bubbling, and perform ultrasound for 2 h; centrifuge the solution, collect the upper layer of liquid to obtain a MXene solution, and freeze-dry the upper layer of liquid to obtain a MXene solid powder, i.e., a MXene nanosheet;

[0047] S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: 1.0 g of artemisia gum was added to a 250 mL four-necked flask, 50 mL of 0.067 mol / L NaOH solution was added and stirred to form a uniform dispersion. Under nitrogen protection, the solution was heated to 70 ° C and stirred at a constant temperature for 1.5 h, 4 mL of an aqueous solution containing 0.1 g of APS initiator was added, stirring was continued for 25 min, and the reaction temperature was reduced to 50 ° C to obtain a reaction system;

[0048] 13 g of itaconic acid, a NaOH solution containing 0.0216 g of MBA cross-linking agent (the concentration of NaOH is 8 mol / L, the amount added is 8.5 mL), and a suspension of 2 g of MXene dispersed in 10 g of water were added dropwise to the reaction system. After the addition was completed, the system was slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction was completed, water was added to wash away excess unreacted MXene, and 2 g of glycerol was added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel.

[0049] Example 2

[0050] The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function provided in a specific embodiment of the present invention is prepared by the following method:

[0051] S1. Preparation of MXene nanosheets: Dissolve 1.6 g lithium fluoride in 20 mL 9 mol / L HCl solution, stir in an ice bath, add 1.0 g Ti3AlC2, stir evenly, and then dissolve in a 40°C oil bath for etching for 48 h; after etching, centrifuge the solution, wash with deionized water, and collect the precipitate by centrifugation; add deionized water to the precipitate, transfer it to a washing bottle, connect a nitrogen gas source for bubbling, and perform ultrasound for 2 h; centrifuge the solution, collect the upper layer of liquid to obtain a MXene solution, and freeze-dry the upper layer of liquid to obtain a MXene solid powder, i.e., a MXene nanosheet;

[0052] S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: 1.0 g of artemisia gum was added to a 250 mL four-necked flask, 50 mL of 0.067 mol / L NaOH solution was added and stirred to form a uniform dispersion. Under nitrogen protection, the solution was heated to 70 ° C and stirred at a constant temperature for 1.5 h, 4 mL of an aqueous solution containing 0.1 g of APS initiator was added, stirring was continued for 25 min, and the reaction temperature was reduced to 50 ° C to obtain a reaction system;

[0053] 13 g of itaconic acid, a NaOH solution containing 0.013 g of MBA cross-linking agent (the concentration of NaOH is 8 mol / L, and the amount added is 8.5 mL), and a suspension of 2 g of MXene dispersed in 10 g of water were added dropwise to the reaction system. After the addition was completed, the system was slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction was completed, water was added to wash away the excess unreacted MXene, and 2 g of glycerol was added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel.

[0054] Example 3

[0055] The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function provided in a specific embodiment of the present invention is prepared by the following method:

[0056] S1. Preparation of MXene nanosheets: Dissolve 1.6 g lithium fluoride in 20 mL 9 mol / L HCl solution, stir in an ice bath, add 1.0 g Ti3AlC2, stir evenly, and then dissolve in a 40°C oil bath for etching for 48 h; after etching, centrifuge the solution, wash with deionized water, and collect the precipitate by centrifugation; add deionized water to the precipitate, transfer it to a washing bottle, connect a nitrogen gas source for bubbling, and perform ultrasound for 2 h; centrifuge the solution, collect the upper layer of liquid to obtain a MXene solution, and freeze-dry the upper layer of liquid to obtain a MXene solid powder, i.e., a MXene nanosheet;

[0057] S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: 1.0 g of artemisia gum was added to a 250 mL four-necked flask, 50 mL of 0.067 mol / L NaOH solution was added and stirred to form a uniform dispersion. Under nitrogen protection, the solution was heated to 70 ° C and stirred at a constant temperature for 1.5 h, 4 mL of an aqueous solution containing 0.1 g of APS initiator was added, stirring was continued for 25 min, and the reaction temperature was reduced to 50 ° C to obtain a reaction system;

[0058] 13 g of itaconic acid, a NaOH solution containing 0.026 g of MBA cross-linking agent (the concentration of NaOH is 8 mol / L, and the amount added is 8.5 mL), and a suspension of 2 g of MXene dispersed in 10 g of water were added dropwise to the reaction system. After the addition was completed, the system was slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction was completed, water was added to wash away the excess unreacted MXene, and 2 g of glycerol was added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel.

[0059] Comparative Example 1

[0060] Based on Example 1, the difference between this comparative example and Example 1 is that MXene nanosheets are not added in this comparative example, and only polyitaconic acid-artemisia gum hydrogel is prepared: 1.0 g of artemisia gum is added to a 250 mL four-necked flask, 50 mL of a 0.067 mol / L NaOH solution is added and stirred to form a uniform dispersion, and under nitrogen protection, the solution is heated to 70° C. and stirred at a constant temperature for 1.5 h, 4 mL of an aqueous solution containing 0.1 g of APS initiator is added, stirring is continued for 25 min, and the reaction temperature is reduced to 50° C. to obtain a reaction system;

[0061] 13 g of itaconic acid and a NaOH solution (the concentration of NaOH is 8 mol / L, and the amount added is 8.5 mL) containing 0.0216 g of MBA cross-linking agent were added dropwise to the reaction system. After the addition was completed, the system was slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction was completed, 2 g of glycerol was added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) hydrogel.

[0062] Comparative Example 2

[0063] Based on Example 1, this comparative example is different from Example 1 in that artemisia gum is not added in this comparative example: after itaconic acid undergoes polymerization reaction under the action of an initiator, a MXene nanosheet dispersion is added to disperse the MXene nanosheets in polyitaconic acid to obtain the product of Comparative Example 2. The added amounts of itaconic acid, initiator, and MXene nanosheets in this comparative example are the same as the corresponding components in Example 1, and the method for polymerization reaction of itaconic acid under the action of an initiator directly adopts the existing technology.

[0064] Comparative Example 3

[0065] Based on Example 1, this comparative example is different from Example 1 in that itaconic acid is not added in this comparative example, and MXene is directly dispersed in artemisia gum: 1.0 g of artemisia gum is added into a 250 mL four-necked flask, 50 mL of 0.067 mol / L NaOH solution is added and stirred to form a uniform dispersion, and under nitrogen protection, the solution is heated to 70°C and stirred at a constant temperature for 1.5 hours, then the suspension of MXene nanosheets is added, and the stirring reaction is continued for 25 minutes to obtain the product of Comparative Example 3.

[0066] Test Example 1

[0067] The electrical conductivity, sand-fixing property and water-retention property of the products prepared in Examples 1-3 and Comparative Examples 1-3 were tested. The test results are shown in Table 1.

[0068] The method for detecting conductivity is: place the sample on a flat electrode, drop an electrolyte into it, and observe the color change of the sample. If an obvious color change occurs, it means that the sample has a certain conductivity.

[0069] Sand fixation: The sand fixation of the present invention includes the study of the surface consolidation effect of sand cakes, the anti-water erosion and anti-wind erosion performance of sand cakes;

[0070] Study on the consolidation effect of sand cake surface: Weigh a certain mass of sand and place it in a watch glass, add 0.5%-3% hydrogel by mass, mix evenly, and obtain a sand cake soaked in hydrogel. After natural drying, take a sample of the sand cake surface for gold spraying and SEM scanning. The sand cake soaked in distilled water is used as a comparison sample.

[0071] Study on the anti-water erosion and anti-wind erosion performance of sand cakes: A series of sand cake samples were prepared using hydrogel samples with different solid contents. First, the surface of the sand cake was moistened, and then the runoff from the center of the sand cake was used for scouring simulation. The runoff scouring was maintained for 1 minute, and then the sand pile was dried in an oven at 60°C for 24 hours to constant weight. The above cycle was repeated 10 times. The anti-water erosion performance was reflected by measuring and calculating the mass residual rate of the sand cake after each cycle.

[0072] Use a hair dryer to gradually increase the wind speed from low to high (strong wind < strong wind < gust of wind < strong wind < gale of wind, wind speed range: 10-23m / s), and blow parallel to the surface of the sand cake mixed with hydrogel. Use an anemometer to monitor the real-time wind speed on the surface of the sand pile and maintain a fixed wind speed for 10 minutes. Observe the damage caused by different wind levels to the consolidation layer, calculate the mass loss rate of the sand pile before and after the test, and evaluate the anti-wind erosion performance.

[0073] Water retention: Study on the water retention performance of sand cakes: Take water-saturated sand cake samples and put them into beakers, and place them in a blast dryer set at 50°C. Weigh the mass of the sand cake samples every two hours until the mass is constant. The water retention rate is obtained by comparing the mass after the mass is constant to the initial mass.

[0074]

[0075]

[0076] Combined with the data in Table 1, it can be seen that the present invention has conductivity, can detect the water content, and has good water retention and sand fixation performance.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function, characterized in that: The method comprises the following components: itaconic acid, artemisia gum, an initiator, a cross-linking agent and MXene nanosheets; Under the action of initiator and cross-linking agent, itaconic acid, artemisia gum and MXene nanosheets are polymerized to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel. The (polyitaconic acid-artemisia gum) / MXene hydrogel is a water-retaining and sand-fixing biomass hydrogel with the function of monitoring water content.

2. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 1, characterized in that: The mass ratio of itaconic acid, artemisia gum and MXene nanosheets is 13:1:

2.

3. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 1, characterized in that: The initiator is ammonium persulfate, and the added amount of the initiator is 10% of the mass of the artemisia gum.

4. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 1, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the added amount of the cross-linking agent is 0.1%-0.2% of the mass of itaconic acid.

5. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 1, characterized in that: The MXene nanosheets are prepared by the following method: Lithium fluoride was dissolved in 9 mol / L HCl solution, Ti3AlC2 was added under stirring in an ice bath, the mixture was stirred evenly and then placed in a 40°C oil bath for etching for 48 h. After etching, the solution was centrifuged and washed with deionized water, and the precipitate was collected by centrifugation. The precipitate was added with deionized water and transferred into a washing bottle, and a nitrogen gas source was connected for bubbling. After ultrasonic treatment for 2 h, the solution was centrifuged, and the upper liquid was collected to obtain a MXene solution. The MXene solution was freeze-dried to obtain MXene nanosheets.

6. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 5, characterized in that: The mass ratio of lithium fluoride to Ti3AlC2 is 1.6:

1.

7. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 1, characterized in that: Prepared by the following method: S1. Preparation of MXene nanosheets; S2. Preparation of (polyitaconic acid-artemisia gum) / MXene hydrogel: Add artemisia gum to a reaction vessel, then add NaOH solution and stir to form a uniform dispersion. Under nitrogen protection, heat the dispersion to 70°C and stir at a constant temperature for 1.5h, then add an aqueous solution of APS initiator, continue stirring for 25min, and reduce the reaction temperature to 50°C to obtain a reaction system. Itaconic acid, NaOH solution containing MBA cross-linking agent and MXene nanosheets are dispersed in water to obtain a suspension, and then the suspension is added dropwise to the reaction system. After the addition is completed, the reaction system is slowly heated to 70°C and stirred at a constant temperature for 2 hours. After the reaction is completed, water is added for washing to obtain a hydrogel system. Finally, glycerol is added to the obtained hydrogel system and stirred evenly to obtain (polyitaconic acid-artemisia gum) / MXene hydrogel.

8. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 7, characterized in that: The concentration of the NaOH solution in the NaOH solution containing the MBA cross-linking agent is 8 mol / L.

9. The water-retaining and sand-fixing biomass hydrogel material with a water content monitoring function according to claim 7, characterized in that: Add the Artemisia sphaerocephala gum into a four-necked flask, then add a 0.067 mol / L NaOH solution and stir to form a uniform dispersion.

Citation Information

Patent Citations

  • Method for preparing composite hydrogel of sodium alginate and artemisia desertorum seed gum

    CN103087334A

  • Granular hydrogel

    CN103724633A

  • Preparation method of multifunctional conductive composite hydrogel based on nanocellulose

    CN115466408A

  • Preparation method and application of ultrahigh-tensile conductive hydrogel material

    CN119119368A